Quality of Anticoagulation with Warfarin in Korean Patients with Atrial Fibrillation and Prior Stroke: A Multicenter Retrospective Observational Study - Hong, Keun-Sik; Kim, Yang-Ki; Bae, Hee-Joon; Nam, Hyo Suk; Kwon, Sun U.; Bang, Oh Young; Cha, Jae-Kwan; Yoon, Byung-Woo; Rha, Joung-Ho; Lee, Byung-Chul; Park, Jong-Moo; Park, Man-Seok; et al. (Journal of clinical neurology (Seoul, Korea), 2017)
The quality of anticoagulation is critical for ensuring the benefit of warfarin, but this has been less well studied in Korean ischemic stroke patients with atrial fibrillation (AF). This study retrospectively analyzed the data of patients who had an AF-related ischemic stroke and were treated with long-term warfarin therapy in 16 Korean centers. The quality of warfarin therapy was primarily assessed by the time in therapeutic range [TTR; international normalized ratio (INR), 2.0-3.0] and additionally by the proportion of INR values within the therapeutic range. The long-term warfarin-treated cohort comprised 1,230 patients. They were aged 70.1±9.7 years (mean±SD), 42.5% were female, and their CHA₂DS₂-VASc score was 4.75±1.41. The TTR analysis included 33,941 INR measurements for 27,487 months: per patients, 27.6 (SD, 22.4) INR measurements for 22.4 (SD, 12.9) months. The mean TTR of individual patients was 49.1% (95% confidence interval, 47.9-50.3%), and the TTR quartiles were <34.5, 34.5-49.1, 49.1-64.5%, and >64.5%. None of the 16 centers achieved a mean TTR of >60%. Of all INR measurements, 44.6% were within the therapeutic range, 41.7% were <2.0, and 13.7% were >3.0. In Korean ischemic stroke patients who had AF, the quality of warfarin therapy was low and might be inadequate to effectively prevent recurrent stroke or systemic embolism.